Cyanide fishing: detection methodologies and physiological effects in coral reef fish in a warming ocean - Vaz, Marcela Carraro de Melo (2019)
Despite being illegal, cyanide fishing is still one of the most commonly employed techniques to stun and capture live coral reef fish in the Indo-Pacific region. Encouraged by the low cost of the chemicals employed, the use of cyanide (CN-) as a fishing technique causes indiscriminate and high mortality on target and non-target species compromising the functional and structural integrity of poisoned coral reef ecosystems. Indeed, CN- is an extremely toxic compound that displays high volatility and low chemical stability, with the study of its toxicokinetics representing a challenging task, as well as the characterization of the physiological processes involved in its detoxification. The reasons detailed justify why the study of CN- detection techniques in vertebrates is remains an up to date research topic. Additionally, it is important to highlight that up to 80% of CN- absorbed by a poisoned organism can be converted into thiocyanate (SCN-) following its excretion through urine- In the present work a detailed review of analytical methodologies currently available for CN- and SCN- detection is presented and its potential application to the detection of illegally caught marine ornamental fish using cyanide poisoning is critically discussed. The present work also reports physiological evidences that fish caught by using this illegal practice in Indo-Pacific coral reefs are still supplying the marine ornamental fish trade (MOFT) in the EU, with the survey performed being the first ever to employ a non-invasive and non-destructive approach screening approach. Taking into account current evidence documenting the warming of world’s oceans and that this threat assumes an eminent and unavoidable character for the regions currently affected by cyanide fishing, the present work also evaluated the effects of CN- exposure in the swimming performance, metabolism and oxidative stress of an emblematic species widely distributed in Indo-Pacific coral reefs and intensely traded by the MOFT, the green damsel, Chromis viridis. Experimental results revealed that if after a sub-lethal exposure to 25 mgL-1 of CN- at 26 °C was already possible to detect a significant decrease in swimming capacity, followed by an increase in oxygen demand, when exposed to the same cyanide concentration in a warming scenario (+3 ºC), the deleterious effects observed were significantly enhanced. Exposure to cyanide and the increase in water temperature were also identified as possible sources of oxidative stress in C. viridis and that these stressors may dramatically affect the resilience of these organisms in Indo-Pacific coral reefs. In conclusion, though this work it is possible to state that if cyanide fishing is not effectively banned across Indo-Pacific coral reefs, the deleterious effects anticipated in the warmer oceans of tomorrow will be devastating in one of the most emblematic marine ecosystems of the planet.